Proceedings of the 2019 Conference of the North 2019
DOI: 10.18653/v1/n19-1140
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Perceived Severity of Cybersecurity Threats Reported on Social Media

Abstract: Breaking cybersecurity events are shared across a range of websites, including security blogs (FireEye, Kaspersky, etc.), in addition to social media platforms such as Facebook and Twitter. In this paper, we investigate methods to analyze the severity of cybersecurity threats based on the language that is used to describe them online. A corpus of 6,000 tweets describing software vulnerabilities is annotated with authors' opinions toward their severity. We show that our corpus supports the development of automa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…The results showed that in their experiments, the NN-based algorithms provide less accuracy than DT-based algorithms. The authors of one paper [ 32 ] presented a method to analyze the severity of CS threats analyzing the language of CS-related tweets through a DL approach. The experiments used a corpus of 6000 tweets containing the description of software vulnerabilities, annotated with the opinions of the authors toward their severity.…”
Section: Related Workmentioning
confidence: 99%
“…The results showed that in their experiments, the NN-based algorithms provide less accuracy than DT-based algorithms. The authors of one paper [ 32 ] presented a method to analyze the severity of CS threats analyzing the language of CS-related tweets through a DL approach. The experiments used a corpus of 6000 tweets containing the description of software vulnerabilities, annotated with the opinions of the authors toward their severity.…”
Section: Related Workmentioning
confidence: 99%
“…Zong et al have collected tweets containing a keyword, "vulnerability", and have applied logistic regression to detect the existence of threats. They have also applied logistic regression and CNN to analyze the extent of threats and the user's opinions on social media about cyber threats [51].…”
Section: Classification By the Cybersecurity Intelligencementioning
confidence: 99%
“…Although cybersecurity has traditionally focused on data created within an organization, opportunities arise from analyzing UD generated outside the organization. For instance, the severity of vulnerabilities can be forecasted analyzing tweets [19]. Tweets can also be analyzed to extract topics, opinions, and knowledge related to security breaches from consumers.…”
Section: Cybersecurity and Unstructured Datamentioning
confidence: 99%